New records of butterflies and their species diversity in four different areas of Savar, Dhaka, Bangladesh (University Journal of Zoology, Rajshahi University, 2012)
Field studies of butterflies were carried out in four different selected areas i.e. Krishnopur, AERE campus, Rajalak Farm and Horters (Part of JU campus) at Savar, Dhaka. Butterflies identified of those areas constituted 158 species belonging 10 families, 87 species of which are newly-recorded in Bangladesh. Numbers of species identified in each family reached 47 in Lycaenidae (30 newly recorded), 32 in Hesperiidae (22 new), 22 in Pieridae (11 new), 19 in Nymphalidae (6 new), 14 in Papilionidae (7 new), 14 in Saytridae (8 new), 5 in Danaidae (1 new), 3 in Riodinidae (1 new), 1 in Acraeidae and 1 newly recorded Amathusiidae. The maximum 130 species and the minimum 65 species were recorded in Krishnopur and Rajalak Farm, respectively. Almost all butterfly families were found to be dominant in Krishnopur. Among the total identified species, 35.44% belonged to very rare (VR) and 20.25% to rare (R) categories, whereas 12.18%, 12.03% and 13.29% species were very common (VC), common (C) and not rare (NR) categories, respectively. It may be that the numbers of butterfly species as well as their fauna vary greatly depending on the floral and ecological conditions in and around the study areas.DOI: http://dx.doi.org/10.3329/ujzru.v30i0.10713Univ. j. zool. Rajshahi Univ. Vol. 30, 2011 pp. 09-15